Overdenture pickup without retaining material; a novel dental technique - Barakat, Noha Waleed; El Far, Mahmoud Mokhtar; Kotb, Ahmed Mustafa Hashim (Frontiers in Dental Medicine, 2025)
This article describes a novel technique for overdenture metal housing pickup for a digitally fabricated overdenture using an extraoral scanner and ExoCAD software. This technique could help the clinician save time and reduce the hassle of extra visits and additional laboratory steps.